A FUNERARY CONTEXT OF MIDDLE HORIZON FROM CERRO COLORADO, HUACHO - van Dalen Luna, Pieter (2015)
The characteristics of a funerary context of the Middle Horizon recovered from the funerary complex of Cerro Colorado, at the southern end of the valley of Huaura is presented. Between 2014 and 2015 the Archaeological Research Project Chancay-Huaral-Atavillos, managed to dig more than 2,000 funerary contexts of this vast funerary complex, the largest in Peru’s central coast.